Circle and Popov Criterion for Output Feedback Stabilization of Uncertain Systems - Benabdallah, A.; Hammami, M. A. (Nonlinear Analysis: Modelling and Control, 2006)
In this paper, we address the problem of output feedback stabilization for a class of uncertain dynamical systems. An asymptotically stabilizing controller is proposed under the assumption that the nominal system is absolutely stable.
Keywords: uncertain system; stabilization; output feedback